Is a woman's first pregnancy outcome related to her years of schooling? An assessment of women's adolescent pregnancy outcomes and subsequent educational attainment in Ghana - Adriana A. E. Biney; Philomena Nyarko (BMC, 2017)
Abstract Background Adolescent pregnancy and childbearing pose challenges to young women's educational attainment. Studies show that while adolescent childbearing reduces educational attainment, not becoming pregnant and resorting to induced abortion when pregnant increases women's educational levels. This study examined relationships between adolescents' resolution of their first pregnancies and subsequent educational outcomes, for all women ages 20-49 years and across three age cohorts: 20-29, 30-39 and 40-49 year olds. Methods Using the 2007 Ghana Maternal Health Survey (GMHS) dataset, we conducted ANOVA, bivariate and multivariate linear regression analyses on 8186 women ages 20-49 years. Women's first adolescent pregnancy outcomes were measured as live births, induced abortions, spontaneous abortions or no pregnancy, while educational attainment constituted their years of schooling. Results Findings showed years of schooling was highest for women who had induced abortions, and lowest for those who experienced live births. Women with live births as teenagers experienced significantly fewer years of schooling compared to their counterparts who terminated their pregnancies. Also, women with miscarriages and stillbirths exhibited levels similar to those who gave birth. Although women with no teenage births had higher educational levels than their childbearing counterparts, controlling for age at first pregnancy resulted in similar years of schooling compared to those who gave birth. Finally, the 30 to 39 year olds were the only age group whose results contradicted those of all women. These findings may be due to the socio-economic and political events that affected women's educational attainment at the time. Conclusions Childbearing during adolescence does impact women's educational attainment levels. Therefore, in addition to encouraging young mothers to continue schooling, all other interventions to help keep young girls in school must focus on preventing and/or delaying their adolescent pregnancies.